Psychometric properties of the of the university sport experiences scale – portuguese - Rathwell,Scott (2021)
ABSTRACT Over the last decades, qualitative methods have dominated Positive Development through sports research. Therefore, valid and reliable quantitative measurement tools are scarce. Additionally, most Positive Development research has focused on youth sport contexts. University sport has been considered a crucial period for a Positive Development approach, and researchers have created the University Sport Experience Survey, which assesses Positive Development in university sport. Although the psychometric properties of USES were confirmed, its validity may be confined to Canadian settings. This study aimed to investigate a cross-cultural adaptation of the University Sport Experiences Survey for a Portuguese-speaking population of university athletes. Our results suggest this confirmed model, containing Portuguese translated items, has strong factorial validity for assessing developmental outcomes of university-aged student-athletes in Brazilian university contexts. Current results support the external validity of University Sport Experiences Survey and offer evidence of the first validated Portuguese assessment tool for assessing Positive Development in university sport.